Development of the Two Stay Two Stray and Jigsaw Model with Learning Videos to Improve Learning Outcomes - Widyawati, Ana; Ahmadi, Farid; Suratno, Suratno (Universitas Negeri Semarang, 2022)
Social studies education in elementary schools is still teacher-centered; it appears that no models or media are employed in social studies education, and learning results have not yet reached the Minimum Competency Criteria (KKM). This study aims to examine the validity, design, and efficacy of the stay-two-stray and jigsaw learning models utilizing learning video media. This is a development study (Four-D Models) comprised of defining, designing, developing, and disseminating stages. Data collection methods are questionnaires, exams and interviews. This study was conducted in grade V SD Negeri Pakuncen and grade I SD Negeri Wonosari in the Pegandon District of the Kendal Regency. The findings demonstrated that establishing two stay-two-stray and jigsaw learning models with video learning to enhance social studies learning outcomes was highly valid, with a syntactic validation score of 92%, content of 87%, and RPP of 95%. The effectiveness of the offering indicates that learning outcomes have improved. Based on the pre- and post-test results, the N-gain test was classified as moderate with a score of 0.60. In addition, the student's emotional and psychomotor learning outcomes improved with excellent criteria. The benefits of research results make it simpler for students to comprehend the material presented by the teacher, improving student learning outcomes. This research concludes that establishing the stay-two-stray and jigsaw learning models with learning videos can increase learning outcomes and that students can collaborate, be responsible for helping one another solve problems, and motivate one another to excel.